2014
DOI: 10.1039/c3ra44507k
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled silver nanoparticles synthesized over the range 5–100 nm using the same protocol and their antibacterial efficacy

Abstract: A systematic and detailed study for size-specific antibacterial efficacy of silver nanoparticles (AgNPs) synthesized using a co-reduction approach is presented here. Nucleation and growth kinetics during the synthesis process was precisely controlled and AgNPs of average size 5, 7, 10, 15, 20, 30, 50, 63, 85, and 100 nm were synthesized with good yield and monodispersity. We found the bacteriostatic/bactericidal effect of AgNPs to be size and dose-dependent as determined by the minimum inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

106
994
8
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,618 publications
(1,128 citation statements)
references
References 52 publications
106
994
8
20
Order By: Relevance
“…They found that smaller particles have larger surface area compared to the larger particles. Interestingly, these results agree with those presented by Martínez-Castañón et al (2008); Lago et al (2011);Zhong et al (2013); Ivask et al (2014) and Agnihotri et al (2014). However, it is not wisely only to compare antibacterial efficacy of AgNPs on the basis of size in different studies, since it will depend on various factors, such as shape, surface chemistry, crystallinity, capping agent, dose of AgNPs, bacterial strains and composition of culture media (Hosseinpour Delavar 2014;Nafisi Bahabadi et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…They found that smaller particles have larger surface area compared to the larger particles. Interestingly, these results agree with those presented by Martínez-Castañón et al (2008); Lago et al (2011);Zhong et al (2013); Ivask et al (2014) and Agnihotri et al (2014). However, it is not wisely only to compare antibacterial efficacy of AgNPs on the basis of size in different studies, since it will depend on various factors, such as shape, surface chemistry, crystallinity, capping agent, dose of AgNPs, bacterial strains and composition of culture media (Hosseinpour Delavar 2014;Nafisi Bahabadi et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the bactericidal properties of AgNPs improved by decreasing AgNPsˊ size (Su et al, 2017a). This phenomenon can be explained by the following; when size of AgNPs decreases, the maximum contact area will increase, and the surface area to volume ratio (SA/ V) for each AgNP will then increase, and this resulting in increasing in relative AgNPs concentration (Agnihotri et al, 2014;Swarnavalli et al, 2017). This can be attributed to higher particle penetration and availability of more area of contact between the bacteria and nanoparticles (Swarnavalli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the nanoparticle implies that it has a large surface area to come in to contact with the bacterial cells; therefore, it will have higher percentage of interaction when compared to bigger particles (Agnihotri et al, 2014;Bondarenko et al, 2013). The formation of Ag-NCHs in the copolymeric hydrogel networks can be expected in our current strategy because the silver salts loaded hydrogels are readily reduced by AAm-LSA hydrogels, which immediately turn into dark brown colour.…”
Section: Identification Of Silver Ion In the Hydrogel Networkmentioning
confidence: 99%